Spy game - Wick, Douglas; Abraham, Marc.; Beckner, Michael Frost; Arata, David; Scott, Tony, 1944-; Redford, Robert; Pitt, Brad, 1963-; McCormack, Catherine; Dillane, Stephen; Bryggman, Larry; Chan, Michael Paul.; Jean-Baptiste, Marianne; et al. (Universal City, Calif. : Universal, 2002)
Retiring CIA agent Nathan Muir recalls his training of Tom Bishop while working against agency politics to free him from his Chinese captors.
Originally produced as a motion picture in 2001.
Special features: deleted scenes with director commentary; script to storyboard; the making of "Spy game" featurette; learn what it takes to become a CIA operative.
Director of photography, Dan Mindel ; editor, Christian Wagner ; music composer, Harry Gregson-Williams ; costume designer, Louise Frogley ; production designer, Norris Spencer.
Robert Redford, Brad Pitt, Catherine McCormack, Stephen Dillane, Larry Bryggman, Michael Paul Chan, Marianne Jean- Baptiste.
MPAA rating: R.
Also issued on VHS.
Keywords: United States. -- Central Intelligence Agency -- Drama; Espionage -- Drama; Feature films; Films for the hearing impaired; Spy films